A medieval songbook : trouvère MS C - Leach, Elizabeth Eva; Mason, Joseph W. (Joseph William), 1991-; Thomson, Matthew P. (Matthew Paul), 1990-; Mittenhuber, Florian; Lévêque-Fougre, Mélanie; Moreno, Paola; Stones, Alison; Gatti, Luca; Lug, Robert; Daniel O'Sullivan, Daniel (Studies in medieval and Renaissance music, 2022)
"The medieval songbook known variously as trouvère manuscript C or the "Bern Chansonnier" (Bern, Burgerbibliothek, Cod. 389) is one of the most important witnesses to musical life in thirteenth-century France. Almost certainly copied in Metz, it provides the texts to over five hundred Old French songs, and is a unique insight into cultures of song-making and copying on the linguistic and political borders between French and German-speaking lands in the Middle Ages. Notably, the names of trouvères, including several female poet-musicians, are found in its margins, names which would be unknown today without this evidence. However, the manuscript has received relatively little scholarly attention, partly because the songs' musical staves remained empty for reasons now unknown, and partly because of where it was copied. This collection of essays is the first to consider C on its own terms and from a range of disciplinary perspectives, including philology, art history, literary studies, and musicology."--From publisher's description.